Development and implementation of the EU grand strategies: sociological, policy, and regional considerations of Agenda 2030 - Fric, Urska (Peter Lang International Academic Publishing Group, 2023)
This book addresses the challenging and exciting issues of the implementation of the European Union's grand strategies, with a particular interest in the implementation of the current Agenda 2030 and its Sustainable Development Goals. It provides insight into the impact of this strategic process on some of the current global issues relevant to the European Union, such as the European and global energy market, food supplies, industrial components etc. Some of the challenges have such a strong short-term impact, that already accepted strategic priorities and decisions are being questioned and re-examined. This is a particularly exciting subject, both as a research topic and as a policy issue.